The Feasibility of Interactive Multimedia Nearpod in Problem-Based Science Education at Elementary Schools - Azizah Rahmi Yudita; Yanti Fitria; Muhammadi Muhammadi; Ulfia Rahmi (Journal of Educational Sciences, 2026)
Science and Social Studies (IPAS) learning in elementary schools faces challenges in presenting abstract concepts that require effective visualization and active student engagement. Therefore, the integration of interactive multimedia is essential to support meaningful learning. This study aims to examine the feasibility of using Nearpod as an interactive multimedia platform oriented toward Problem-Based Learning (PBL) to improve fifth-grade students’ conceptual understanding and digital literacy skills. The study employed a research and development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Product feasibility was evaluated through expert validation involving three validators: a subject matter expert, a linguistics expert, and a media expert. The validation results showed feasibility percentages of 93.33% for material aspects, 95.00% for language aspects, and 97.37% for media aspects, all categorized as highly valid. The overall average feasibility score reached 95.23%, indicating that the Nearpod-based interactive multimedia is valid and suitable for use. The findings demonstrate that this multimedia effectively supports problem-based science learning, facilitates the understanding of abstract concepts, and enhances students’ digital literacy. Therefore, the developed multimedia is feasible for implementation in fifth-grade elementary schools with minor revisions based on expert recommends.